Phase Transition in Binary Mixture of Bose Gases - Phat, Tran Huu; Hoa, Le Viet; Anh, Nguyen Tuan; Long, Nguyen Van (Communications in Physics, 2012)
Based on the Cornwall-Jackiw-Tomboulis (CJT) effective action approach a theoretical formalism is established for studying the Bose-Einstein condensation (BEC) in a binary mixture of Bose gases. The effective potential, which preserves the Goldstone theorem, is found in the Hartree-Fock (HF) approximation. This quantity is then used to consider the equation of state (EOS) and the phase transition of the system